KOMPOSISI DAN KEPADATAN SAMPAH LAUT (MARINE DEBRIS) PANTAI PURUS, K OTA PADANG - Yusra Yusra; Rici Erlini (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2021)
The remainder of human activity in the form of solids, whether deliberately disposed of or not into the marine environment is called marine debris. This study aims to determine the weight, composition and density of marine debris in Purus, Padang City. Sampling was carried out from February to April 2021. Determination of the location by purposive sampling using line transect sampling method. Waste is separated based on macro and meso sizes and then the weight and amount of each type of waste is calculated. From the research results found 9 thypes of waste, namely types of plastic waste, plastic foam, cloth, glass and ceramics, metal, paper and cardboard, rubber and wood and another materials. There were 9805 pieces of waste with a total weight of 27170.74 gr, consisting of 21554.7 gr of macro waste and 5616.4 gr of meso waste. Based on the weight of waste, the most dominant types found were cloth (9311.6 gr) for macro waste and 5616.04 gr for meso waste. The highest density is found in the type of wood with WD02 code as much as 50.92 pieces/m2 for macro waste and WD06 as many as 226.8 pieces/m2 for meso waste.